Post-Soviet Transitions of the Planned Socialist Towns: Visaginas, Lithuania - Baločkaitė, Rasa (Studies of Transition States and Societies, 2010)
Visaginas, formerly Sniečkus, (Lithuania) was built as a planned socialist town and a satellite settlement to the Ignalina Nuclear Power Plant. Both the plant and the town were established in order to integrate Lithuania into the All-Union economic structures via the energy supply system,. The specific characteristics of the town were a particular mono industry, high living standards, ethnic composition (mostly Russian speaking migrants, Lithuanians as minority), absence of any history prior to 1973 and strong pro-Soviet attitudes. For years, it was a success story and the vanguard site of the socialism. After the declaration of Lithuanian Independency in 1990, the town became the site of tensions and uncertainties. The aim of this research study is to illuminate how post-Soviet transition has been experienced by this particular type of community shaped by socialism. Community experiences are retrospectively reconstructed via content analysis of the local media. The particular characteristics of the town (ethnic composition, employment structure, etc.) made the process of transition extremely complicated. While other planned socialist towns established new identities and new trajectories of development, in the case of Visaginas, not the future, but the past played a crucial role in shaping the town’s identity.